The use of Yttrium-90 Ibritumomab Tiuxetan (90Y-IT) as a consolidation therapy in high-risk patients with diffuse large B-cell lymphoma ineligible for autologous stem-cell transplantation - Jurczak, Wojciech; Kisiel, Elżbieta; Sawczuk-Chabin, Joanna; Centkowski, Piotr; Knopińska-Posłuszny, Wanda; Khan, Omeir (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : To evaluate the efficacy and safety of Yttrium-90 Ibritumomab Tiuxetan ( 90 Y-IT) as a consolidation therapy in the management of DLBCL. Material and methods : Patients with primary refractory or high-risk DLBCL (n = 18), ineligible for autologous stem-cell transplantation, were included in a retrospective study performed at three centers by the Polish Lymphoma Research Group (PLRG). All patients (mean age 61, range 35–82) either didn’t achieve a complete response or didn’t complete the scheduled therapy due to its complications. Response rates (CR, PR, SD, PD) according to Cheson criteria, overall survival (OS), progression-free survival (PFS) and adverse effects of radioimmunotherapy were analyzed. Results: Consolidation radioimmunotherapy increased the CR rate from 38% (n = 7) to 82% (n = 15). One patient remained in PR, one patient remained in SD, while one patient remained in PD. During a median follow-up of five years, 11 patients (62%) were alive with no recurrence, 4 patients (22%) were alive with relapse while 3 patients (16%) died. There was no statistically significant difference in PFS between those in CR and those in PR before 90 Y-IT. Conclusions : Radioimmunotherapy is an effective consolidation therapy for high risk/refractory DLBCL patients and worthy of further investigation in prospective trials.